IL-22-dependent dysbiosis and mononuclear phagocyte depletion contribute to steroid-resistant gut graft-versus-host disease in mice - Qingxiao Song (Nature Portfolio, 2021)
Pathogenesis of steroid-resistant gut acute graft-versus-host-disease (SR-Gut-aGVHD) remains unclear., Here the authors show in mouse models that dysbiosis caused by the expansion of Th/Tc22, as well as depletion of CX3CR1hi mononuclear phagocytes resulted from the reduction of Th/Tc1, contributes to SR-Gut-aGVHD onset.